The use of ultrasound sliding sign for prediction of adhesions in women undergoing repeated caesarean section - Ali H. Yosef; Alaa Eldin A. Youssef; Ahmed M. Abbas; Ahmed A. Mohamed; Shimaa M. Mostafa; Mostafa N. Ibrahim (Taylor & Francis Group, 2023)
We carried out this study to validate the use of ultrasound sliding sign to predict intraperitoneal adhesions in women undergoing repeated caesarean section (CS). A cross-section study was performed in women with at least one CS scheduled for an elective CS. We used the sliding sign of the uterus against the anterior abdominal wall to assess intraperitoneal adhesions, positive sliding sign if uterus moved freely and a negative sliding sign if limited mobility. The obstetrician was blind to the ultrasound results, asked to report if adhesions were absent or present during CS to validate accuracy of the sliding sign. We examined 120 women, negative sliding was reported in 54 patients, positive sliding in 66 women. The presence of intra-abdominal adhesions was confirmed in 44/54 cases assigned to the high-risk group, while the prediction of low risk for adhesions confirmed in 66/66 patients with a sensitivity of 100%, specificity of 86.84%. Sliding sign is an effective method to detect intra-abdominal adhesions in women with a history of repeated caesarean delivery.Impact statement What is already known on this subject? There has been a dramatic increase in the caesarean section (CS) rate worldwide; repeated CSs may be associated with intraperitoneal adhesions that result in difficulty during the procedure and may be related to bowel or bladder injuries and neonatal morbidities. What do the results of this study add? The sliding sign by ultrasound has a sensitivity of 100%, specificity of 86.84%, a positive predictive value of 81.5, a negative predictive value of 100, and accuracy of 91.67, considering it rapid, easy and reliable method for prediction of intraperitoneal adhesions. What are the implications of these findings for clinical practice and/or future research? The use of sliding sign by ultrasound in cases with repeated CSs offers a good predictor tool for presence of intraperitoneal adhesions and subsequently avoid severe sequels during surgery and good preparation.